The Relationship of Sensory Processing of Children with Developmental Dysphasia with Burnout and Self-Esteem of Parents - Petrovic, Jelena; Zorić, Jelena; Petrović - Lazić, Mirjana (Specijalna edukacija i rehabilitacija, 2023)
The relatioinship of sensory processing of children with developmental dysphasia with burnout and self-esteem of parentsJelena R. Petrovića, Jelena M. Zorićb, Mirjana Petrović LazićcaUniversity of Defence - Military Academy, Belgrade, SrbijabInstitute for Psychophysiological and Speech-Language Disorders "Prof. Dr. Cvetko Brajović", Belgrade, SerbiacUniversity in Belgrade - Faculty of Special Education and Rehabilitation, Belgrade, Serbia  Introduction. Sensory processing difficulties can pose a risk for the development of language and speech disorders in the earliest period and require professional intervention and intense involvement of parents in homework with children with developmental dysphasia which might cause parental burn-out and lower level of their personal self-esteem, when parents are not able to help, not only to the children, but themselves too. Aim. The aim of the research was to examine the relationship between sensory sensitivity of children with developmental dysphasia and the characteristics of parents. Method. The sample consisted of 50 parents of children aged 3 to 6 years. Questionnaires were used in the research to assess the characteristics of sensory processing: The child sensory profile 2, Parental Burnout Inventory, Rosenberg self-esteem scale. Measures of descriptive statistics and Pearson 's correlation coefficient were used in data processing. Results: The results of the research show that the level of parental burnout is relatively low (parents showed high level of personal accomplishment (M = 4.16, SD = .67), mild level of emotional exaustion (M = 2.34, SD = .78) and low level of emotional distancing (M = 1.72, SD = .72), but also that they are characterized by lower self-esteem (M = 3.11, SD = .34). Also, self-esteem and burn-out are not related. On The Sensory profile, subscales of behavior elements are highly correlated, while intesity of correlations in subscales of basic system of processing oscilates. There is weak correlation between general self-esteem of parents with subscales body posture and behavior. Conclusion. The obtained results were discussed in the context of practical pedagogical implications, considering that, if the difficulties in the child's functioning are not eliminated in the preschool period, the child's departure to school may be delayed or long-term difficulties in learning may appear.
Keywords: speech disorder; developmental dysphasia; sensory profile; special language disorder